Drug-resistance and population structure of plasmodium falciparum across the Democratic Republic of Congo using high-throughput molecular inversion probes - Aydemir,O; Janko,M; Hathaway,NJ; Verity,R; Mwandagalirwa,MK; Tshefu,AK; Tessema,SK; Marsh,PW; Tran,A; Reimonn,T; Ghani,AC; Ghansah,A; et al. (Journal of Infectious Diseases, 2018)
A better understanding of the drivers of the spread of malaria parasites and drug resistance across space and time is needed. These drivers can be elucidated using genetic tools. Here, a novel molecular inversion probe (MIP) panel targeting all major drug-resistance mutations and a set of microsatellites was used to genotype Plasmodium falciparum infections of 552 children from the 2013–2014 Demographic and Health Survey conducted in the Democratic Republic of the Congo (DRC). Microsatellite-based analysis of population structure suggests that parasites within the DRC form a homogeneous population. In contrast, sulfadoxine-resistance markers in dihydropteroate synthase show marked spatial structure with ongoing spread of double and triple mutants compared with 2007. These findings suggest that parasites in the DRC remain panmictic despite rapidly spreading antimalarial-resistance mutations. Moreover, highly multiplexed targeted sequencing using MIPs emerges as a cost-effective method for elucidating pathogen genetics in complex infections in large cohorts.